Remarks on some Echiniscidae (Heterotardigrada) from New Zealand with the description of two new species - Pilato, Giovanni; Binda, Maria Grazia; Lisi, Oscar (Zootaxa, 2005)
Some specifications are provided about nine species of Echiniscidae from New Zealand including descriptions of two new species: Echiniscus arthuri sp. nov. and Echiniscus elaeinae sp. nov. Echiniscus arthuri sp. nov. has plate sculpture of the merokensis type but is different in some details from the sculpture of this species. Also present are lateral filaments A, spines C and D, and filaments E and dorsal filaments C d and spines D d . Echiniscus elaeinae sp. nov. has uniform plate sculpture consisting of circular dimples; lateral filaments A, long lateral spines C, D, E and dorsal spines C d and D d are present. It differs from E. jamesi Claxton, 1996 in having a simple, not double, plate sculpture, in the presence of dorsal spines C d and D d and in the lateral appendages appearing as spines (in E. jamesi they are filaments up to 100 µm long).